Prison and Non-Prison Sanctions in Cases of Defamation through Social Media - Purnomo, Didik; Widyawati, Anis; Kusuma, Bagus Hendradi (Indonesia Media Law Review, 2025)
The increase in online defamation in Indonesia in line with the growing number of internet users, which is often responded to with prison sentences of up to 4 years based on the Electronic Information and Transactions Law, has raised a debate regarding the effectiveness and proportionality of such punishments. This article aims to compare the effectiveness of prison sanctions versus non-prison sanctions such as fines, community service, and their alignment with the principles of restorative justice and the 2023 Criminal Code. The research method uses a comparative-normative approach by analyzing the rulings on defamation cases via Facebook, the ITE Law, and regulatory changes in the Criminal Code (Law No. 1/2023). The study results show that the defendants were sentenced to prison (2–8 months), only 3 received probation, the 2023 Criminal Code (effective 2026) abolishes prison sentences for minor offenses, switching to fines (maximum Rp10 million) or community service, online defamation has now become a complaint-based crime following the changes to the ITE Law in 2016. In conclusion, short-term prison sentences are less effective because they have the potential to sacrifice freedom of expression and have minimal preventive impact, while non-custodial sentences are more suitable for minor cases in line with the adoption of restorative justice. Recommendations include amendments to the Electronic Information and Transactions Law (UU ITE) to integrate alternative sanctions of fines or community service, prioritizing mediation as a preliminary step, and socializing the limits of digital freedom.